Introduction - Teye, Joseph Kofi (African Human Mobility Review, 2021)
In recognition of the benefits of migration and the challenges associated withits management, many governments and development partners have, in recentyears, been discussing how to develop effective frameworks for migrationgovernance at the national, regional and international levels (Mangala, 2017).As a result of the increasing realisation that population mobility can contributeto socio-economic transformation of both migrant sending and receivingareas, migration management was, in 2015, included in the 2030 Agenda forSustainable Development and the Sustainable Development Goals (SDGs)(OECD/ILO 2018), marking the first time that migration is formally integratedinto the global development agenda.